Mechanisms of surface roughening of commercial purity titanium during ultrasonic impact treatment; Materials Science and Engineering: A; Vol. 647 - Panin A. V. Alexey Viktorovich; Kazachenok M. S. Marina Sergeevna; Kozelskaya A. I. Anna Ivanovna; Hairullin (Khayrullin) R. R. Rustam Ravilievich; Sinyakova E. A. Elena Aleksandrovna (2015, 2015)
Title screen